PENGARUH PERBANDINGAN TALAS KIMPUL (Xanthosoma sagittifolium) DENGAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP KARAKTERISTIK SATE LILIT KELADI - Putu Lisa Adinda Putri; Ni Made Yusa; I Ketut Suter (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This study aims to determine the effect of xanthosoma and white oyster mushroom on the characteristics of sate lilit keladi, and to know the right ratio of xanthosoma and white oyster mushroom on the characteristics of sate lilit keladi. The experimental design used was completely randomized design with the treatment ratio of xanthosoma and oyster mushroom, which consists of 6 levels such as: 100% : 0%, 90% : 10%, 80% : 20%, 70% : 30%, 60% : 40%, 50% : 50%. The treatment was repeated 3 times to obtained 18 units of the experiment. The data were analysed by analysis of variance and if the treatment had an effect on the variable then continued with Duncan test. The result showed xanthosoma and white oyster mushroom ratio had a significant effect on water content, ash content, fat content, protein content, carbohydrate content, coarse fiber content, hardness, color (hedonic), aroma (hedonic), texture (hedonic and scoring), taste (hedonic and scoring) and overall acceptance (hedonic). Comparison of 50% xanthosoma and 50% white oyster mushroom had the best characteristics, with 52,86 % water content, 3,31 % ash content, 6,52% protein content, 24,57% fat content, 12,74% carbohydrate content, 35,88% coarse fiber content, 0,11 kg/5mm hardness, color liked, aroma liked, texture mushy and rather liked, typical taste rather keladi and liked and overall acceptance liked.